The German organ transplant scandal: unwritten rules of organizational wrongdoings - Pohlmann, Markus; Höly, Kristina; Trombini, Maria Eugenia (Social science & medicine, 2022)
Using data from organ transplant medicine in Germany, we propose a method for understanding the content of unwritten rules supportive of violations of written rules in light of the “German Organ Transplant Scandal”. Grounded in the sociology of organizational crime, we reconstruct the cultural repertoires of medical professionals working with organ allocation when confronted with the applicable guidelines using collective mindset analysis. Four dimensions of cognitive and normative rules of interpretation were identified and discussed as a an occupational-professional form of deviance. Apart from not relying on data from the alleged perpetrators and still gazing at the latent structures of meaning behind misconduct, our approach offers a more general methodological framework for empirical studies of the unwritten rules at work in an organizational field where wrongdoing has been reported.
Gesehen am 04.01.2022
Available online 19 November 2021